TGFβ1-induced hedgehog signaling suppresses the immune response of brain microvascular endothelial cells elicited by meningitic Escherichia coli - Jinrui Sun; Ruicheng Yang; Jiyang Fu; Dong Huo; Xinyi Qu; Chen Tan; Huanchun Chen; Xiangru Wang (Cell Communication and Signaling, 2024)
Abstract Background Meningitic Escherichia coli (E. coli) is the major etiological agent of bacterial meningitis, a life-threatening infectious disease with severe neurological sequelae and high mortality. The major cause of central nervous system (CNS) damage and sequelae is the bacterial-induced inflammatory storm, where the immune response of the blood-brain barrier (BBB) is crucial. Methods Western blot, real-time PCR, enzyme-linked immunosorbent assay, immunofluorescence, and dual-luciferase reporter assay were used to investigate the suppressor role of transforming growth factor beta 1 (TGFβ1) in the immune response of brain microvascular endothelial cells elicited by meningitic E. coli. Result In this work, we showed that exogenous TGFβ1 and induced noncanonical Hedgehog (HH) signaling suppressed the endothelial immune response to meningitic E. coli infection via upregulation of intracellular miR-155. Consequently, the increased miR-155 suppressed ERK1/2 activation by negatively regulating KRAS, thereby decreasing IL-6, MIP-2, and E-selectin expression. In addition, the exogenous HH signaling agonist SAG demonstrated promising protection against meningitic E. coli-induced neuroinflammation. Conclusion Our work revealed the effect of TGFβ1 antagonism on E. coli-induced BBB immune response and suggested that activation of HH signaling may be a potential protective strategy for future bacterial meningitis therapy. Video Abstract